A PATIENT REPORTED OUTCOME MEASURES-BASED COMPOSITE INDEX (RAPID3) FOR THE ASSESSMENT OF DISEASE ACTIVITY IN ANKYLOSING SPONDYLITIS - Cinar, M.; Yilmaz, S.; Cinar, F. I.; Koca, S. S.; Erdem, H.; Pay, S.; Simsek, I. (Bmj Publishing Group, 2014)
[Abstract Not Available]
15th Annual European Congress of Rheumatology (EULAR) -- JUN 11-14, 2014 -- Paris, FRANCE